2013
DOI: 10.1021/ol402805f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of β-Hydroxy-α-amino AcidsviaDiastereoselective Decarboxylative Aldol Reaction

Abstract: A straightforward metal-free synthesis of anti-β-hydroxy-α-amino acids is described. The organic base-mediated decarboxylative aldol reaction of cheap, readily available α-amidohemimalonates with various aldehydes afforded under very mild conditions anti-β-hydroxy-α-amido esters in high yields and complete diastereoselectivity. Simple one-pot subsequent transformations enabled the corresponding anti-β-hydroxy-α-amino acids or in a few examples their syn diastereomers to be obtained directly using epimerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…It is thanks to these molecules that β-hydroxy-α-amino acids are synthesized. [14] β-hydroxy-α-amino acids are important biomolecules and building blocks for the synthesis of many biologically active compounds such as ristocetin and teicoplanin of the vancomycin antibiotic family. In order to differentiate these compounds by TWIM-MS, dimers [2M + X II -H] + and trimers [3M + X II -H] + in which X II is a divalent transition metals (Mn II , Fe II , Co II , Ni II , Cu II and Zn II ) were formed and analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is thanks to these molecules that β-hydroxy-α-amino acids are synthesized. [14] β-hydroxy-α-amino acids are important biomolecules and building blocks for the synthesis of many biologically active compounds such as ristocetin and teicoplanin of the vancomycin antibiotic family. In order to differentiate these compounds by TWIM-MS, dimers [2M + X II -H] + and trimers [3M + X II -H] + in which X II is a divalent transition metals (Mn II , Fe II , Co II , Ni II , Cu II and Zn II ) were formed and analyzed.…”
mentioning
confidence: 99%
“…For this work, the cis ((2R, 3S)-ethyl-2-benzamido-3-hydroxy-3-(4nitrophenyl)propanoate) and trans ((2S, 3S)-ethyl-2-benzamido-3hydroxy-3-(4-nitrophenyl)propanoate) diastereomers were synthesized according to an original procedure recently published. [14] The compounds were dissolved separately in methanol to a concentration of 1 mg mL -1 (2.8 mM). Metal salts used were manganese (II) chloride tetrahydrate (MnCl 2 .4H 2 O), iron (II) sulfate heptahydrate (FeSO 2 .7H 2 O), cobalt (II) chloride hexahydrate (CoCl 2 .6H 2 O), nickel (II) chloride (NiCl 2 ), copper (II) chloride (CuCl 2 ), and zinc (II) chloride (ZnCl 2 ).…”
mentioning
confidence: 99%
“…We have recently demonstrated that MAHOs 1 can act as effective nucleophiles with several aldehydes in the decarboxylative aldol reaction . To expand this methodology for the direct synthesis of α,β‐diamino esters, we started our investigation of the decarboxylative Mannich reaction with MAHO 1a and tosyl imine 2a as model substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Decarboxylative studies are quite new in the asymmetric synthesis and there are only a few examples with bifunctional organocatalyst. 40,41 In 2013, Rouden and coworkers showed the excellent diastereoselective (only anti product) synthesis of antiβ-hydroxy-α-amino acids from α-amidohemimalonates with various aldehydes by using different organic bases (Scheme 23). 19.…”
Section: Reactionmentioning
confidence: 99%